PEDAGOGICAL PRINCIPLES OF SPIRITUAL-MORAL ACTIVITY - B. X. O’razov (Galaxy International Interdisciplinary Research Journal, 2022)
The principles of spiritual and moral education of students and young people in our independent country are to build a humane democratic society; It is a set of didactic tools aimed at theoretical and practical study of methods, forms and methods of improving the effectiveness of spiritual and enlightenment work. This principle can be connected to various links of educational work in educational institutions.